FACTORS ASSOCIATED WITH THE OCCURENCE OF STUNTING IN CHILDREN AGED 12-35 MONTH IN THE DIY PROVINCE - Made Ayu Lely Suratri; Vebby Amelia Edwin; Endang Indriasih; Nurhayati; Anni Yulianti (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Stunting is a condition of failed growth in children characterized by significantly short stature relative to their age. Stunting occurs due to inadequate and unbalanced nutrient intake, and it can be influenced by other factors such as illness, poor sanitation, limited access to clean water, and an environment that does not support optimal child growth. The purpose of this study was to know the factors associated with the occurrence of stunting for children aged 12-35 months in the DIY Province. This study is a further analysis of the 2021 Indonesian Nutritional Status Study data for the Province of DIY. The design of the research was stratified two-stage sampling. Stunting data collection was carried out through interviews with parents of children using a questionnaire and measuring the height of the children by local enumerators. Bivariate analysis to know the relationship between the independent variable and the dependent variable. Meanwhile, to know the factors associated with the occurrence of stunting in children, a multivariate analysis was carried out. The result showed that there wasa significant relationship between stunting with the age of mothers, difficulty transportation to healthcare, monitoring and development of children, and the mother receiving nutritional counseling, p-value≤ 0.05. Age of children, gender of children, place of residence, education of mothers, and occupation of mothers, had no significant association with the occurrence of stunting, p-value> 0.05. The factors associated with the occurrence of stunting for the children were the age of mothers, difficulty transportation to healthcare, monitoring, and development of children, and the mother receiving nutritional counseling. It is necessary to increase the role of posyandu as a forum that helps the government to improve public health, in this case reducing stunting rates in toddler.